THERMAL COMFORT IN OFFICE BUILDINGS - Ancuta Nadia JURCO; Liviu Iacob SCURTU (Journal of Industrial Design and Engineering Graphics, 2019)
In this paper is studied the thermal comfort in an office room. The first part of the paper presents the state of the art of numerical methods and graphical determination of the thermal comfort in buildings. Using the advanced modelling techniques, in the second part of the paper, the office volume with the ventilation and evacuation systems are modelled. The simulation is achieved using the CFD module from the SolidWorks software, where is assigned the mechanical properties to all components. In this paper are studied three simulation cases. The obtained results from the first case are compared with the results from the second and third case. In the last part of the paper are presented the conclusions of this study.